Prions and Prion-Like Pathogens in Neurodegenerative Disorders - Caterina Peggion; Maria Catia Sorgato; Alessandro Bertoli (Pathogens, 2014)
Prions are unique elements in biology, being able to transmit biological information from one organism to another in the absence of nucleic acids. They have been identified as self-replicating proteinaceous agents responsible for the onset of rare and fatal neurodegenerative disorders—known as transmissible spongiform encephalopathies, or prion diseases—which affect humans and other animal species. More recently, it has been proposed that other proteins associated with common neurodegenerative disorders, such as Alzheimer’s and Parkinson’s disease, can self-replicate like prions, thus sustaining the spread of neurotoxic entities throughout the nervous system. Here, we review findings that have contributed to expand the prion concept, and discuss if the involved toxic species can be considered bona fide prions, including the capacity to infect other organisms, or whether these pathogenic aggregates share with prions only the capability to self-replicate.